IMPLEMENTATION OF P5 ACTIVITIES IN THE INDEPENDENT CURRICULUM OF SMA MUHAMMADIYAH 1 RAMBIPUJI ON HISTORY LEARNING WITH THE THEME OF LOCAL WISDOM OF TOBACCO HISTORY AT THE JEMBER MUSEUM: IMPLEMENTASI KEGIATAN P5 DALAM KURIKULUM MERDEKA SMA MUHAMMADIYAH 1 RAMBIPUJI PADA PEMBELAJARAN SEJARAH DENGAN TEMA KEARIFAN LOKAL SEJARAH TEMBAKAU DI MUSEUM JEMBER - Ilmiatul Janah; Rina Rohmawati; Agi Ma’ruf Wijaya (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to find out and understand the P5 (Pancasila Student Profile Strengthening Project) activities in the Independent Curriculum implemented at SMA Muhammadiyah 1 Rambipuji, especially in learning history with the theme of local wisdom that focuses on the history of tobacco at the Jember Museum. The implementation of P5 is one of the components of the character development project of Indonesian students which aims to transfer Pancasila values, so that the goal of implementing P5 in the Independent Curriculum can be achieved, namely positioning students as Pancasila learners. This study uses a qualitative descriptive methodology. Data collection techniques were carried out through interviews involving history teachers and students, visits to museums and documentation. The results of the study show that visits to tobacco museums have a significant positive impact on history learning. A visit to the museum not only enriches the students' learning experience but also enhances their knowledge of the history and culture of the region, ultimately helping them grow as Pancasila students and build their identity.